Pengembangan dan Pengujian Sistem Pengiriman Barang dengan Konsep Customer Relationship Management pada PT. Khatulistiwa Transogi - Yoseph Tajul Arifin; Norma Yunita; Andera Fausti; Desti Wahyunita (ICSE (Institute of Computer Sciences and Engineering), 2020)
Timeliness of delivery, ease of tracking the status of shipping information and guaranteed security of goods is a measure of the success of freight forwarding companies, fast service and ease of getting information can improve business quality and customer loyalty to the company. In the business process of PT Khatulistiwa Transogi, several problems were found that hampered the activities of the company engaged in the delivery of goods, such as errors in input data, transaction data search, data management, customer management, data security and data loss that was enchanted by the current system. This is not yet optimal, the use of paper that still dominates business activities and data integration is not well. The application of information technology in the field of freight forwarding can help the efficiency and effectiveness of a company business process. This research aims to develop an information system as well as to apply customer relationship management methods with a case study in the freight forwarding company PT. Khatulistiwa Transogi. The results of application quality measurement surveys that have been implemented get good ratings from system users, namely the criteria for the ability of users to communicate with software, software operation, accuracy, minimize errors, simplify activities, and storage efficiency, although there are still 2 other criteria that are felt by the user such as the lack of training received by 5 out of 8 users and the inefficient execution time stated by 1 in 8 users.